Pengaruh Tingkat Suku Bunga Kredit dan Non Perfoming Loan (NPL) terhadap Capital Adequacy Ratio (CAR) pada Bank Negara Indonesia (BNI) - A. A. Sri Purnami; Renya Ignasia Kali (Warmadewa Economic Development Journal (WEDJ), 2018)
This research aims is to prove the correlation interest of credit and Non Performing Loan to Capital Adequacy Ratio in Bank Negara Indonesia using times series data since 2011-2015. Multiple regression linear is used to analyze data. Result of this research shows that in simultan interest of credit and non perfoming loan have a signifficant effect to Capital Adequacy Ratio. In partial, interest of credit have a negative and signifficant effect, and Non Performing Loan have a positive and signifficant effect to Capital Adequacy Ratio. R2 shows result 54,9 percent which means 54,9 percent interest of credit and Non Performing Loan can describe Capital Adequacy Ratio. While, 45,1 percent are describe by variables outside the model.